Taking the Hinge off: An Approach to Effector-Less Monoclonal Antibodies - Jamie Valeich; Dan Boyd; Manu Kanwar; Daniel Stenzel; Deblina De Ghosh; Arpa Ebrahimi; James Woo; Jenny Wang; Alexandre Ambrogelly (Antibodies, 2020)
A variety of Fc domain engineering approaches for abrogating the effector functions of mAbs exists. To address some of the limitations of the current Fc domain silencing approaches, we are exploring a less commonly considered option which relies on the deletion of the hinge. Removal of the hinge domain in humanized IgG1 and IgG4 mAbs obliterates their ability to bind to activating human Fc gamma receptors I and IIIA, while leaving their ability to engage their target antigen intact. Deletion of the hinge also reduces binding to the Fc neonatal receptor, although Fc engineering allows partial recovery of affinity. Engineering of the CH3 domain, stabilizes hinge deleted IgG4s and prevents Fab arm exchange. The faster clearing properties together with the pacified Fc make modality of the hinge deleted mAb an appealing solution for therapeutic and diagnostic applications.